Unpacking the Influence of Job Satisfaction on Lecturers’ Performance: Evidence Among Private Higher Educational Sector - Tep, Sopheng; Rosli, Rozaini Binti (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This research defines lecturers’ perception of job satisfaction and explores the influence of job satisfaction on lecturers’ performance in the private higher educational sector in Phnom Penh, Cambodia. Methodology: The researcher applied descriptive statistics (M, S.D.) to assess lecturers’ perceptions of their job satisfaction levels. At the same time, multiple linear regression was employed to explore the influence of job satisfaction on lecturers’ performance. Furthermore, the researcher used the questionnaire of 36 items to survey lecturers physically in four private higher educational sector. A total of 304 lecturers teaching during the 2024–2025 academic year participated in this survey. Main Findings: The study revealed a moderate positive relationship between job satisfaction and lecturers’ performance (R = 0.67, Adjusted R² = 0.445, p = 0.000, N = 304). These findings align with previous research, indicating that job satisfaction plays a vital role in enhancing lecturers’ performance. Furthermore, the results displayed that extrinsic job satisfaction factors, such as negotiable salaries and proper working conditions, were found to have a more significant impact on performance compared to intrinsic job satisfaction. Novelty/Originality of this study: This study makes a significant contribution by expanding on previous research that highlights the critical role of job satisfaction in enhancing lecturers’ performance. It uniquely identifies the impact of extrinsic job satisfaction factors—such as salary, working conditions, and interpersonal relationships—as key drivers of higher lecturers’ performance. The research also suggests that future studies explore additional influences, such as leadership styles and external factors, in promoting lecturers’ performance.